Understanding college success through the lens of first-generation students in China: An interpretative phenomenological analysis - Li, Ruihua; Che Hassan, Norlizah; Saharuddin, Norzihani; Sha, Ouyang (Elsevier, 2024)
Background: First-generation college students face unique challenges in navigating the higher education system, and understanding their perceptions of college success is crucial for providing appropriate support. Objective: This qualitative study aimed to explore the perceptions of 15 first-generation college students regarding college success and to identify the factors they consider important for achieving success in college. Method: Semi-structured interviews were conducted with the participants, and the data were analyzed using interpretative phenomenological analysis. Results: This study explores the varied perceptions of success among first-generation college students (FGCS) through five themes: Academic Achievement, Personal Development, Personal Well-being, Personal Fulfillment, and Career Success. Conclusion: This study provides valuable insights into the perceptions of first-generation college students regarding college success. The identified themes shed light on the multifaceted nature of success in higher education. These findings have implications for supporting first-generation college students and developing targeted interventions to enhance their overall success and well-being.